Salicylic acid does not alleviate salt stress on physiological indicators and growth of guava - Nogueira de Lacerda, Cassiano; Geovani Soares de Lima; Lauriane Almeida dos Anjos Soares; Hans Raj Gheyi; Pedro Dantas Fernandes; Silva , Idelvan José da (Comunicata Scientiae, 2023)
In the semi-arid region, the quality of water for irrigation stands out as a limiting factor for the expansion of agriculture. Thus, it is extremely important to search for alternatives that minimize the effects of salt stress on plants. Foliar application of salicylic acid stands out among these strategies. In this context, the objective of this study was to evaluate the gas exchange, photosynthetic pigments, and growth of guava as a function of irrigation water salinity and exogenous application of salicylic acid in the post-grafting stage. The experiment was conducted under greenhouse conditions, in a randomized block experimental design, in a 2 × 4 facto rial scheme, corresponding to two levels of electrical conductivity of irrigation water (0.6 and 3.2 dS m-1) and four concentrations of salicylic acid (0; 1.2; 2.4 and 3.6 mM), with three replicates. Irrigation with water of 3.2 dS m-1 caused reductions in transpiration, CO2 assimilation rate, instantaneous water use efficiency and instantaneous carboxylation efficiency of guava, at 150 days after transplanting. Water with electrical conductivity of 3.2 dS m-1 reduced the growth in stem diameter and the absolute and relative growth rates, as well as the relative water content, and chlorophyll a and b contents of guava plants. The interaction between water salinity levels and salicylic acid concentrations did not influence the physiological indices and growth of guava in the postgrafting phase.